2020
DOI: 10.1007/s00125-020-05223-3
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoglycaemia and absolute risk of cause-specific mortality in individuals with type 2 diabetes: a UK primary care observational study

Abstract: Aims/hypothesis Several pathophysiological mechanisms would suggest a causal link between hypoglycaemia and cardiovascular death; conversely, current knowledge would not support a causal relationship with other causes of death. To clarify the nature and the magnitude of the association between hypoglycaemia and death, we investigated the 5 year mortality risks for cardiovascular disease, cancer and other causes in individuals with type 2 diabetes admitted to hospital for a severe hypoglycaemic episode. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
(60 reference statements)
1
15
0
Order By: Relevance
“…The relationship between SH and cardiovascular mortality continues to generate controversy as to whether it is a direct cause, or is a marker of serious underlying illness that predisposes to this metabolic event. 38 Although this relationship may be bi-directional, 39 the present study supports SH as a marker of poor prognosis in those with high comorbidity burden, particularly in people with T2D and non-DM individuals. Most deaths were from non-cardiovascular causes, particularly sepsis, multi-organ failure, cancer and advanced frailty, and the comorbidity burden was significantly greater among those who died.…”
Section: Discussionsupporting
confidence: 49%
“…The relationship between SH and cardiovascular mortality continues to generate controversy as to whether it is a direct cause, or is a marker of serious underlying illness that predisposes to this metabolic event. 38 Although this relationship may be bi-directional, 39 the present study supports SH as a marker of poor prognosis in those with high comorbidity burden, particularly in people with T2D and non-DM individuals. Most deaths were from non-cardiovascular causes, particularly sepsis, multi-organ failure, cancer and advanced frailty, and the comorbidity burden was significantly greater among those who died.…”
Section: Discussionsupporting
confidence: 49%
“…Historically, the use of SUs as a monotherapy or in combination has, in general, been perceived to increase the risk for major hypoglycemic events as compared to other diabetes medications [71][72][73]. The risk is higher for most insulin secretagogues than for other DM drugs, and is in fact a strong indicator of poor prognosis among T2D patients [74]. Accumulating evidence has, however, consistently demonstrated that, among SU drugs, gliclazide poses the lowest risk for episodes of major hypoglycemia [30,75,76], and that this risk is comparable to those posed by other commonly used secondline therapeutic drugs [32,34,55].…”
Section: Major Hypoglycemia and Ramadan Studiesmentioning
confidence: 99%
“…Our sample is broadly representative of our larger cohort of people with type 2 diabetes and when compared with a population level cohort including those with type 2 diabetes ( n = 74,222) derived from the Clinical Practice Research Datalink (CPRD) in the United Kingdom, the average BMI (30.6 kg/m 2 (CODEC) vs. 30.1 kg/m 2 (CPRD)), HbA1c (6.9% (CODEC) vs. 6.9% (CPRD)) and age (65 (CODEC vs. 67.7 (CPRD)) were broadly similar 40 . However, our study does have limitations.…”
Section: Discussionmentioning
confidence: 99%